2020
DOI: 10.7759/cureus.10268
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Utility and Clinical Implications of Bronchoalveolar Lavage in Cancer Patients With Febrile Neutropenia and Lung Infiltrates

Abstract: Introduction Febrile neutropenia (FN) is a dreaded complication of cancer chemotherapy and frequently associated with respiratory infections. Flexible bronchoscopy (FB) serves as a useful diagnostic tool in this regard. Objective To determine the diagnostic yield, safety and clinical implications of bronchoalveolar lavage (BAL) in cancer patients with FN, having lung infiltrates on radiographic chest imaging. Methods We reviewed medical records of FN patients who underwent FB at Shaukat Khanum Memorial Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…By investigating 88 BAL fluids of AL patients with clinically suspected infection and radiological infiltrates under broad-spectrum antibiotic and antifungal treatment, positive microbiological BAL fluids with clinically relevant pathogens were obtained in 47% of our cases. These results are consistent with previously reported studies describing 39–54% of positive BAL fluids [ 13 , 20 , 21 , 22 , 23 ]. However, in some studies, lower rates, with a range of approximately 23–32% of positive BAL fluids, were reported [ 12 , 14 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…By investigating 88 BAL fluids of AL patients with clinically suspected infection and radiological infiltrates under broad-spectrum antibiotic and antifungal treatment, positive microbiological BAL fluids with clinically relevant pathogens were obtained in 47% of our cases. These results are consistent with previously reported studies describing 39–54% of positive BAL fluids [ 13 , 20 , 21 , 22 , 23 ]. However, in some studies, lower rates, with a range of approximately 23–32% of positive BAL fluids, were reported [ 12 , 14 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Of note, despite the extensive empiric anti-infective treatment in our study population, in nearly every second BAL fluid (47%), relevant pathogens could be isolated. Aspergillus fumigatus was the most detected pathogen albeit the empiric anti-fungal treatment in every patient, indicating the high risk of invasive aspergillosis in patients with AL underlying previous reported data [ 20 , 22 , 25 ]. Remarkably, no multi-resistant pathogens were isolated despite the administration of broad-spectrum antibiotics and anti-fungal agents.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Several other studies have reported similar modification rates, ranging from 38.2% to 63.3%, with effective outcomes in a majority of patients. 20,22,28 The impact of BAL on reducing unnecessary antimicrobial use, especially in regions with high drug resistance and limited resources, is important without affecting response rates. We observed that change in antimicrobial therapy resulted in a 17.3% ( P = .063) increase in clinical response compared with no change in therapy, demonstrating the high clinical relevance of BAL findings.…”
Section: Discussionmentioning
confidence: 99%
“…BAL may lead to changes in clinical management in the range of 50% of cases and in general were very well tolerated (26)(27)(28). One study comparing BAL to lung biopsy in pediatric HSCT patients at a single institution found that 40% of the 101 BALs revealed a pathogen, while 94% of the 19 lung biopsies identified an etiology (29).…”
Section: Invasive Samplingmentioning
confidence: 99%